Hepatitis B virus incidence and risk factors among Human Immunodeficiency Virus-1 negative men who have sex with men in Kenya. - Wahome, E; Ngetsa, C; Mwambi, J; Gelderblom, H; Manyonyi, G; Micheni, M; Hassan, A; Price, M; Graham, S; Sanders, E (Oxford University Press, 2016)
No data exist on hepatitis B virus (HBV) incidence among African men who have sex with men (MSM). We tested plasma samples archived between 2005 and 2014 for HBV core antibody or surface antigen seroconversion in a cohort of 312 initially human immunodeficiency virus (HIV)-1-negative MSM with no evidence of prior HBV infection. Hepatitis B virus incidence was 6.0/100 person-years (95% confidence interval [CI], 3.9-9.1). Hepatitis B virus acquisition was associated with being uncircumcised (adjusted incidence rate ratio [aIRR], 5.0; 95% CI, 1.5-16.8), recent HIV-1 acquisition (aIRR, 2.9; 95% CI, 1.1-7.7), rape (aIRR, 5.0; 95% CI, 1.2-20.4), and any tertiary education (aIRR, 3.2; 95% CI, 1.1-9.7). African MSM have a substantial risk of HBV acquisition and require vaccination urgently.